Penggunaan Peta Konsep Sebagai Instrumen Penilaian Terhadap Pemahaman Konseptual Peserta Didik Melalui Model Pembelajaran PDEODE Pada Materi Asam Basa - Chandra, Annisa; Suhartono, Suhartono; Fitriani, Ella (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This research is aimed to find out the uses of concept maps as instruments of assessment students’ conceptual understanding through PDEODE learning model on acid-base materials. This research uses qualitative methods, conducted at SMAN Jakarta in the second semester. The participants were the 36 students of grade XI MIPA in one of Senior High School in Jakarta. The treatment is given based on Predict-Discuss-Explain-Observe-Discuss-Explain (PDEODE). The research data was obtained from the assessment of concept maps, observations, and interviews. The assessment of concept map uses the Novak and Gowin assessment rubric which added concepts. The results showed concept map can be used as an instrument for assessing conceptual understanding and misconception of students. The PDEODE learning model affects the process of students in understanding the concept of acid-base. Conceptual understanding of students is classified as medium and low criteria. Through concept maps can be identified misconceptions experienced by students especially on the theory of acid-base. Keywords Concept Maps, Conceptual Understanding, PDEODE, Acid-Base, Assessment